2020
DOI: 10.1186/s12871-020-01135-2
|View full text |Cite
|
Sign up to set email alerts
|

Complications of cricothyroidotomy versus tracheostomy in emergency surgical airway management: a systematic review

Abstract: Background: Airway guidelines recommend an emergency surgical airway as a potential life-saving treatment in a "Can't Intubate, Can't Oxygenate" (CICO) situation. Surgical airways can be achieved either through a cricothyroidotomy or tracheostomy. The current literature has limited data regarding complications of cricothyroidotomy and tracheostomy in an emergency situation. The objective of this systematic review is to analyze complications following cricothyroidotomy and tracheostomy in airway emergencies. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Cricothyroidotomy can have serious complications like endotracheal tube misplacement, tracheal and vocal cord injury, vocal cord granuloma and paralysis, pneumonia, retropharyngeal abscess and late complications like tracheal and subglottic stenosis. 18 This incident was complicated by a posterior tracheal tear and minor injury to the vocal cords, which is a known complication in emergency cricothyroidotomy by conventional palpation method, even in experienced hands. The tracheal tear could perhaps have been avoided by prior use of airway ultrasound and also by directing the scalpel perpendicular to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Cricothyroidotomy can have serious complications like endotracheal tube misplacement, tracheal and vocal cord injury, vocal cord granuloma and paralysis, pneumonia, retropharyngeal abscess and late complications like tracheal and subglottic stenosis. 18 This incident was complicated by a posterior tracheal tear and minor injury to the vocal cords, which is a known complication in emergency cricothyroidotomy by conventional palpation method, even in experienced hands. The tracheal tear could perhaps have been avoided by prior use of airway ultrasound and also by directing the scalpel perpendicular to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Heute wird bei elektiven Eingriffen die Tracheotomie bevorzugt, um Kehlkopfverletzungen zu vermeiden. Aufgrund der vergleichsweise einfachen Identifizierung des Ligamentum conicum und eines wahrscheinlich geringeren Blutungsrisikos gilt die Koniotomie jedoch weiterhin als Standardzugang in der Notfallsituation, obwohl eine geringere Rate an Akutkomplikationen gegenüber der Tracheotomie in klinischen Studien bislang nicht belegt werden konnte 4 .…”
Section: Historieunclassified
“…Additional studies have found cricothyrotomy complication rates ranging from 41.9% to 57% and post‐procedural mortality ranging from 44.4% to 87% 7‐10 . A systematic review of surgical airways evaluated early and late complications regardless of location of procedure or provider experience and found that tracheostomy had more long‐term complications compared to cricothyrotomy 11 . Information regarding immediate and late complications, factors including provider experience, and associated morbidity and mortality is needed.…”
Section: Introductionmentioning
confidence: 99%